1989
DOI: 10.1200/jco.1989.7.10.1528
|View full text |Cite
|
Sign up to set email alerts
|

A prospective ophthalmic evaluation of patients with acute myeloid leukemia: correlation of ocular and hematologic findings.

Abstract: We report the results of a prospective 2-year study of the ocular manifestations of myeloid leukemia. Fifty-three patients underwent complete ophthalmic evaluation prior to the initiation of treatment as well as during the course of their disease. All ocular abnormalities were confined to the retina and optic nerve and were present in 34 patients, 30 of whom had either hemorrhages or cotton-wool spots alone or in combination. These findings were unrelated to age, sex, French-American-British (FAB) classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 8 publications
5
62
0
5
Order By: Relevance
“…Therefore, we feel that the correlation of haematological parameters with the occurrence of retinal lesions was appropriate. Other researchers have noted an association between anaemia and the presence of retinal haemorrhages (Gibson 1938;Culler 1954;Dwivedi et al 1986;Karesh et al 1989;Guyer et al 1989;Abu el-Asrar et al 1996). However, no significant association between anaemia and the occurrence of IRH (1996) reported that ALL patients with cotton-wool spots had significantly lower haemoglobin levels than patients without such lesions.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we feel that the correlation of haematological parameters with the occurrence of retinal lesions was appropriate. Other researchers have noted an association between anaemia and the presence of retinal haemorrhages (Gibson 1938;Culler 1954;Dwivedi et al 1986;Karesh et al 1989;Guyer et al 1989;Abu el-Asrar et al 1996). However, no significant association between anaemia and the occurrence of IRH (1996) reported that ALL patients with cotton-wool spots had significantly lower haemoglobin levels than patients without such lesions.…”
Section: Discussionmentioning
confidence: 94%
“…Geralmente envolve os tecidos oculares mais tardiamente sendo a retina, órbita, nervo óptico e trato uveal os locais mais acometidos [3][4][5] .…”
Section: Discussionunclassified
“…Alterações retinianas ocorrem em 30% a 90% dos casos de leucemia 3,4 . Dilatações e aumento de tortuosidade dos vasos e hemorragias retinianas são os achados mais comuns.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…В научной литературе имеются проспективные исследова-ния, доказывающие последнее утверждение [87]. От 14 до 53 % пациентов с лейкозом имеют оф-тальмологические проявления заболевания уже на момент постановки онкогематологического диагноза [52]. При посмертном гистологическом исследовании глазного яблока и орбиты специ-фические изменения обнаруживаются в 28-80 % [55].…”
Section: том 9 № 2 2016unclassified